A CALPHAD-Informed Enthalpy Method for Multicomponent Alloy Systems with Phase Transitions - Scherr, Robert; Liepold, Philipp; Markl, Matthias; Körner, Carolin (Modelling, 2024)
Solid–liquid phase transitions of metals and alloys play an important role in many technical processes. Therefore, corresponding numerical process simulations need adequate models. The enthalpy method is the current state-of-the-art approach for this task. However, this method has some limitations regarding multicomponent alloys as it does not consider the enthalpy of mixing, for example. In this work, we present a novel CALPHAD-informed version of the enthalpy method that removes these drawbacks. In addition, special attention is given to the handling of polymorphic as well as solid–liquid phase transitions. Efficient and robust algorithms for the conversion between enthalpy and temperature were developed. We demonstrate the capabilities of the presented method using two different implementations: a lattice Boltzmann and a finite difference solver. We proof the correct behaviour of the developed method by different validation scenarios. Finally, the model is applied to electron beam powder bed fusion—a modern additive manufacturing process for metals and alloys that allows for different powder mixtures to be alloyed in situ to produce complex engineering parts. We reveal that the enthalpy of mixing has a significant effect on the temperature and lifetime of the melt pool and thus on the part properties.
CRIS-Team Scopus Importer:2024-04-05
Keywords: CALPHAD; enthalpy method; enthalpy of mixing; in situ alloying; lattice Boltzmann method; powder bed fusion additive manufacturing